Prognostic impact of right ventricular strain in isolated severe tricuspid regurgitation. (3rd October 2022) - Hinojar Baydes, R; Garcia-Martin, A; Gonzalez-Gomez, A; Monteagudo, J M; Garcia-Lunar, I; Rivas, S; Sanroman, M; Pardo, A; Sanchez-Recalde, A; Zamorano, J L; Fernandez-Golfin, C
Abstract: Background: Right ventricular (RV) systolic function is determinant in the evaluation of patients with severe tricuspid regurgitation (TR). Timely detection of RV dysfunction with conventional 2D echocardiography is challenging. RV strain has emerged as an accurate and sensitive tool for evaluation of RV function with the capability of detecting subclinical RV dysfunction. Purpose: This study was aimed to evaluate the prognostic value of RV strain parameters in consecutive stable patients with severe TR. Methods: Consecutive patients in stable clinical status with at least severe TR (severe, massive or torrential TR) evaluated in the Heart Valve Clinic following a comprehensive clinical protocol were included. Patients with previous episodes of heart failure or scheduled for TV intervention were excluded. RV systolic function was measured with conventional echocardiographic indices (RV fractional area change [FAC], tricuspid annular plane systolic excursion [TAPSE], DTI S wave [`S]) and with Speckle-tracking echocardiography (STE) derived automatic peak global and free wall longitudinal strain (RV-GLS and RV-FWLS respectively) using the EPIQ system (Philips Medical Systems, Andover, Massachusetts). A combined endpoint of hospital admission due to heart failure (HF) or all-cause mortality was defined. The interobserver variability of RV strain was assessed in 20 randomly selected patients. Results: A total of 176 patients were included in this study. Strain parameters detected higher percentage of RV dysfunction compared to conventional indices (figure 1). After a median follow-up of 28 months (IQR: 15–48 months), n=65 patients (37%) reached the combined endpoint. 65 (37%) were admitted for right heart failure and 8% of the population (n=14) died. Cumulative event-free survival was significantly worse in patients with impaired RV-GLS and RV-FWLS. Conventional indices of RV systolic function were not associated with outcomes (p>0.05 for all). In a multivariable analysis (in a model including NYHA class, BNP values, biplane VC, RV end-diastolic area, and RV-FWLS), RV-FWLS was an independent predictors of heart failure and CV mortality (figure 1 and 2; LR χ 2 : 40.2, p<0.001). Inter-observer agreements for RV strain values were high (intraclass correlation coefficient for RV-GLS and RV-FWLS, r=0.96 and r=0.98 respectively) Conclusion: Clinical outcomes demonstrate that RV strain parameters are superior to conventional indices of RV function in patients with isolated ≥ severe TR and absence of previous episodes of heart failure. Among all parameters of RV function, RV-FWLS is the strongest independent predictor of mortality and HF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto Carlos III